The Impact of Food Safety Incidents Across Brands: The Case of the Peter Pan Peanut Butter Recall. (November 2014) - Bakhtavoryan, Rafael; Capps, Oral; Salin, Victoria
Abstract : The effect of negative publicity on consumer demand for brands is examined in the context of recall of a peanut butter brand as a result of pathogen contamination. The recall was associated with negative impacts for the implicated brand and positive effects on the leading competitor brand. Consumers responded to the foodborne illness outbreak within three weeks. The case demonstrates that consumer response is an incentive for companies to prevent safety lapses and that the problems of one brand do not necessarily harm rivals within the category.